Efficacy and Safety Concerns with Sn-Mesoporphyrin as an Adjunct Therapy in Neonatal Hyperbilirubinemia: A Literature Review - Prakar Poudel; Sudhir Adhikari (Hindawi Limited, 2022)
Neonatal hyperbilirubinemia is a frequently observed clinical situation that, sometimes, may result in complications ranging from mild neurodevelopment impairment to serious outcome of kernicterus. The rationale logic of heme oxygenase enzyme inhibition to lower bilirubin levels is intriguing. In compliance with that rationale, metalloporphyrin was discovered. After successful results in in-vitro and animal studies, tin mesoporphyrin is now under phase II clinical trial to test for preventive and therapeutic efficacy in unconjugated hyperbilirubinemia. This review evaluates in-vitro studies, animal studies, and clinical trials for the efficacy and safety of tin analogues of metalloporphyrin. Few alternatives to metalloporphyrins are also available, synchronizing with the same rationale logic of inhibition of bilirubin production, which need further research.